2001
DOI: 10.1111/j.1574-6968.2001.tb10774.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of nasal carriage ofStaphylococcus aureusas risk factor for human skin infections

Abstract: The present study was designed to investigate the significance and the relationship between nasal carriage of Staphylococcus aureus and staphylococcal skin infections. Thirty-one S. aureus strains, isolated from 12 patients with chronic and recurrent skin infections, one patient with septicemia and one patient with otitis externa were studied. The staphylococcal strains were isolated from the site of infection and from the anterior nares of each patient. The identity of both strains of each pair could be demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Previous studies have shown that S. aureus originating in the nasal cavity may contaminate e.g. dialysis access sites [5,6]. Our study suggests that the source of contamination of leg ulcers may be the patients’ anterior nares and further implicates that removal of infecting S. aureus from the leg ulcer may be very difficult if the reservoir (the nasal cavity) remains contaminated.…”
Section: Introductionmentioning
confidence: 62%
“…Previous studies have shown that S. aureus originating in the nasal cavity may contaminate e.g. dialysis access sites [5,6]. Our study suggests that the source of contamination of leg ulcers may be the patients’ anterior nares and further implicates that removal of infecting S. aureus from the leg ulcer may be very difficult if the reservoir (the nasal cavity) remains contaminated.…”
Section: Introductionmentioning
confidence: 62%
“…Colonization with S. aureus is a demonstrated risk factor for subsequent SSTI. 1618 However, the relationship between S. aureus colonization of household contacts and development of S. aureus infections in index patients is unknown. These relationships must be understood to devise appropriate prevention and treatment guidelines and to implement measures to prevent S. aureus transmission and infections within households.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus colonization is a demonstrated risk factor for the development of SSTI 46. Measures to eradicate S. aureus carriage, including intranasal mupirocin and bathing with chlorhexidine antiseptic, have been evaluated in the prevention of nosocomial infections.…”
mentioning
confidence: 99%